Songbird diversity and poaching pressure in Biha Resort, Bukit Barisan Selatan National Park, Sumatra, Indonesia - ADINDA FARAH CAHYANI; JANI MASTER; LUHUR SEPTIADI; NUNING NURCAHYANI; RIKHA ARYANIE SURYA; WILLIAM MARTHY (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Cahyani AF, Master J, Septiadi L, Nurcahyani N, Surya RA, Marthy W. 2025. Songbird diversity and poaching pressure in Biha Resort, Bukit Barisan Selatan National Park, Sumatra, Indonesia. Biodiversitas 26: 6447-6457. Bird diversity in Sumatra, Indonesia, is increasingly threatened by poaching, yet comprehensive data remain limited, especially in key conservation areas such as Biha Resort within Bukit Barisan Selatan National Park (BBSNP). This study provides a baseline assessment of bird diversity, species composition, and population density across three monitoring sites in Biha Resort, an area previously prone to bird poaching, conducted in July 2024 using the point count method. Analyses included survey completeness, diversity indices (Shannon-Wiener H’, Simpson D, Pielou’s E), and Hutcheson’s t-test to compare sites, while distance sampling was used to estimate density. A total of 69 species were recorded, with survey completeness of 73.4%. Diversity indices varied across sites, with significant differences between site A and the others (p<0.05). Overall values were H’: 3.792, E: 0.896, and D: 0.030, indicating healthy habitat conditions capable of supporting rich variety of bird species. Songbirds dominated the community, and only 12 species had measurable density, with Arachnothera longirostra being the most abundant. As a baseline, this survey provides essential reference data for long-term monitoring of bird populations. Continued monitoring is needed to evaluate the effectiveness of an Integrated Prevention Model designed to reduce poaching pressure and support bird conservation in the region.